2021
DOI: 10.1002/alr.22828
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of self‐reported symptoms and psychophysical tests in coronavirus disease 2019 (COVID‐19) subjects experiencing long‐term olfactory dysfunction: a 6‐month follow‐up study

Abstract: scale (VAS) and the 22-item Sino-Nasal Outcome Test (SNOT-22). 1 However, self-reported OD poorly correlates with olfactory tests such as Sniffin' Sticks (S'S). 3 The aim of this study is to provide a prospective longterm assessment of COVID-19-related OD using PROMs 4 and S'S 5 and to investigate their correlation. METHODSPatients with laboratory-confirmed SARS-CoV-2 infection and OD/TD were selected from our Infectious Disease

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
29
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 12 publications
(23 reference statements)
7
29
0
1
Order By: Relevance
“…The damage caused to the epithelium decreases the trophic support that it provides to the neurons, thus causing alterations of the sense of smell [39]. The results of the present study together with those of a previous one [15], showing mainly an involvement of T, seem to confirm that OD in COVID-19 patients has an end-organ failure pathogenesis [40].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The damage caused to the epithelium decreases the trophic support that it provides to the neurons, thus causing alterations of the sense of smell [39]. The results of the present study together with those of a previous one [15], showing mainly an involvement of T, seem to confirm that OD in COVID-19 patients has an end-organ failure pathogenesis [40].…”
Section: Discussionsupporting
confidence: 85%
“…Very few studies have employed objective olfactory tests to assess the presence of olfactory dysfunction [14]. As the correlation between subjective smell perception and the results of the olfactory tests can be low or even absent [15], relying only on patients' reports on olfactory and gustatory dysfunctions may lead to biased results and underestimation of the real incidence of these symptoms in COVID-19 patients, also taking into consideration the fact that not all patients that present with olfactory dysfunction exhibit total anosmia. Some of them only exhibit a partial loss of smell, which, if very mild, may go unnoticed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bordin et al found the lack of correlation when observing the olfactory recovering in patients with COVID‐19. 71 Le Bon et al showed inconsistency between self‐reporting gustatory dysfunction and “Taste Strips” test score. 72 However, these studies alone cannot lead to a firm conclusion due to limitations of time‐frame between onset of symptoms and performance of psychophysical tests.…”
Section: Discussionmentioning
confidence: 99%
“…72 However, these studies alone cannot lead to a firm conclusion due to limitations of time‐frame between onset of symptoms and performance of psychophysical tests. 71 , 72 A visual analog scale has been used for the quantitative evaluation of OGD in the included studies and demonstrated a significant difference in self‐rated olfactory and gustatory function between positive and negative COVID‐19 groups. 8 , 23 , 29 , 30 , 32 , 51 , 52 , 53 , 55 Psychophysical tests have been modified from previously validated tests 8 or developed as rapid assessment tools 7 , 9 to assess OGD in patients with suspected COVID‐19.…”
Section: Discussionmentioning
confidence: 99%